Bovine infertility - a field oriented categorisation based on investigation among crossbred cattle in a district of Kerala - KUTTY, C IBRAHEEM; RAMACHANDRAN, K (The Indian Journal of Animal Sciences, 2014)
Animals (500) were examined for gynaecological reasons and the infertility conditions were suitably categorised for easier description. Out of these animals, 374 (75%) were diagnosed to be infertile cases, which included 148 cows and 226 heifers. Infertility cases mainly were of 2 types based on manifestation such as anoestrum (65%) and repeat breeding (35%). Out of the 242 anoestrum cases, 178 (74%) were true' anoestrum and rest (26%) were cases of false anoestrum. Among 132 repeat breeding animals 26 (20%) had ovulatory disturbances, 70 (53%) had reproductive tract infections (RTI) and in 33 (25%) both ovulatory disturbances and RTI together were seen. Major reasons for the conditions were nutritional deficiencies, reproductive tract infections and functional disturbances suspected out of elimination of males. It is concluded that most infertility conditions among crossbred cattle are arising out of management defects either of the farmers or technician, which in turn form indirect Consequences of intensive crossbreeding and widespread AI programme.